Using literary texts to teach students' reading comprehension - Saeed, Ibrahim Mohammed; Liu, Mengqin (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The term literary text is often used to refer to aesthetic written work with standard language, compelling plots and complicate character development that can appeal to readers. Great literary texts not only entail people to read and write well but also give them the chance to broaden their horizons and perspectives. In the field of education, the study of literary texts allows students to foster critical thinking, develop literacy and cultivate imagination. It has only been since the 1980s that literature has been used in teaching English in English as a Foreign Language (EFL) classroom. Generally speaking, studying literature usually close relates to reading comprehension, which is a multifaceted act of interpreting and understanding what you are reading. In reading classes, the use of literary text has been a matter of concern in teaching process in order to achieve more efficient and more constructive reading comprehension goals. However, there are some problems faced by both teachers and students in the teaching and learning process of acquiring English reading comprehension skills such as misperceptions of literature, restrictions of the curriculum and confusions of text selections. This paper is meant to emphasize the significance of literary texts to teach reading in the EFL class and its effects on improving students’ reading comprehension skills. Based on previous studies of literature, using literary texts to teach reading can be a uniquely powerful instruction method in teaching English in EFL classrooms, particularly in developing students’ reading skills and deepening reading comprehension.